Boethius's "De topicis differentiis" - Boethius, -524 (Cornell University Press, 1978)
In Ciceronis Topica and De topicis differentiis are Boethius's two treatises on Topics (loci). Together these two works present Boethius's theory of the art of discovering arguments, a theory that was highly influential in the history of medieval logic.